Level of urbanization and habitat type, and not patch size, influence predacious arthropod diversity patterns of urban grasslands in South Africa - Bianca Greyvenstein (MBI & UNS Solo, 2021)
Abstract. Greyvenstein B, Botha M, van den Berg J, Siebert SJ. 2021. Level of urbanization and habitat type, and not patch size, influence predacious arthropod diversity patterns of urban grasslands in South Africa. Biodiversitas 22: 4078-4094. Predacious arthropods provide a valuable ecosystem service within urban environments by suppressing pest numbers. However, urban ecological studies largely ignore this functional group and its diversity and species composition patterns. Some studies have been published regarding these patterns, however they were mostly done in Australia, Europe and America, thus an African perspective is lacking. Our aim was to address the gap in African literature by quantify the differences in predacious arthropod species richness and diversity within urban green space in varying urbanization intensities, habitat types of grassland and patch sizes in South Africa. Various indices were considered to examine the effect of urbanization on the diversity patterns of Chrysopidae (Neuroptera), Mantodea, Araneae and Coccinellidae (Coleoptera). Study sites included three levels of urbanization represented by population density, two types of urban grasslands (i.e., ruderal and fragmented grassland) and a peri-urban rangeland grassland as control, and a wide range of patch sizes. Our results indicated that an increase in urbanization intensities was associated with increased abundance of predacious arthropod taxa. Also, that urban and peri-urban grasslands had similar predacious arthropod species richness and diversity, but differed in species composition. No relationship was found between patch size and arthropod diversity or composition. Thus, predacious arthropod abundances are influenced by the level of urbanization and their species composition is influenced by the type of urban grassland (ruderal or fragmented), which are important considerations for future urban planning/management and conservation strategies. This study gives a South African perspective and indicates that despite the lack of assigned function of urban green spaces, they sustain diverse and distinct predacious arthropod communities, which in turn fulfill various roles in a functioning ecosystem.